Beginning at the end decadence, modernism, and postcolonial poetry - Stilling, Robert, 1977- (Harvard University Press, 2018)
In 1857, Charles Baudelaire described the colonial condition as one in which "a nation begins with decadence and starts off where the others leave off." A century later, Frantz Fanon would argue that postcolonial artists were "beginning at the end," following the West's "path of negation and decadence" while skipping the inventive phase of youth. In Beginning at the End, Robert Stilling argues that for writers and artists such as Chinua Achebe, Agha Shahid Ali, Derek Walcott, Wole Soyinka, Yinka Shonibare, Bernardine Evaristo, and Derek Mahon, the notion of being caught between the decadence of Europe and the unformed possibilities of postcolonial cultures marks the founding condition for a postcolonial poetics. For these figures, the idea of decadence would haunt their attempts to carve out a place for the arts in postcolonial society, forcing them to negotiate between their own sense of the demands of art and the pressure to conform to a revolutionary politics. In reimagining the role of poetry and the visual arts in the formation of national cultures, these artists turned toward the oppositional politics and anti-realist aesthetics of writers such as Oscar Wilde to affirm a commitment to artifice and the imagination while fending off the charge of decadence associated with modernism and the idea of art for art's sake. Taking a transnational approach, Beginning at the End expands the study of literary decadence beyond fin-de-siècle Europe, and demonstrates the continuing importance to postcolonial thought of figures such as Oscar Wilde, Henry James, J.-K. Huysmans, Walter Pater, and Max Beerbohm.--